Stories of the Visually Impaired EFL Learners in Turkey - Ayşe Nur Ekinci; Kadriye Dilek Bacanak; Ömer Gökhan Ulum (Ömer Gökhan Ulum, 2024)
Sighted and blind individuals live alongside each other in different parts of the world. In the basic principle of being human, sighted and blind individuals are not different from each other. Visually impaired individuals differ from sighted individuals only in terms of their special needs arising from their visual impairment. Meeting these special needs is important for visually impaired individuals to have equal opportunities with sighted individuals in various fields. As a basic human right, both parties need to access to quality and meaningful education. This situation is not different in foreign language education. Hence, this study aimed to explore what visually impaired students have been through in the process of learning English as a foreign language. The participants of the study, which was designed as a narrative research, were 5 visually impaired university students who studied English as a foreign language. In the study, which was designed as a qualitative research, data were collected through semi-structured interviews. The results of the research revealed that visually impaired students have had both positive and negative experiences during their English education.